(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
This study was carried out to evaluate the quality of whole milk powder repacked and sold in the market of Khartoum State, Sudan. The study involved the collection of 27 samples of repacked whole milk powder from three brands in three different batches according to sampling time (batch 1 samples were collected in October, batch 2 samples were collected in November and batch 3 samples were collected in December). The samples were then subjected to chemical and microbiological analysis. The results showed that fat and titratable acidity were not significantly different between the brands, while the protein and moisture were higher in brand B and the ash was high in brand C. Time of sampling did not significantly affect fat, moisture and titratable acidity, while the protein content was high in batch 2 and ash content was high in batches 2 and 3. The brand significantly affected total viable bacterial, coliform bacterial and yeasts and moulds counts, and there was no significant variation in lipolytic and proteolytic bacteria between the three brands. Sampling time had a significant effect on total viable bacteria, coliform bacteria and lipolytic bacteria. However, no significant effect of sampling time was observed in proteolytioc bacteria and yeasts and moulds in the three brands.